3 - La contribution des Universités dans la mise en œuvre des ODD au Sénégal : le cas de l’Université Alioune Diop de Bambey - Mamadou Saliou Mbengue, (African Sociological Review, 2019)
This text is a contribution to the implementation of the SDGs in Senegal in general, in the locality of Bambey in particular. Inspired by the integrated approach of the SDGs of the Hydro-Québec Institute for Environment Development and Society of Laval University, two workshops are conducted in July 2017 at the University Alioune Diop Bambey (UADB), first with the University occupants (students, technical administration and service staff, and teachers) and then with Bambey civil society actors. These two workshops for the appropriation and implementation of the 17 SDGs resulted in results whose social, economic and environmental analysis highlighted, for each framework of analysis of the issues aggregated to the SDGs. Direct and indirect links are established between the targeted SDG and others by providing rationale for all positive and negative linkages. The preferred prioritization system is based on a broad consensus on the SDGs for which the UADB and the Bambey community must mobilize to build the University into a sustainable campus and boost local development. To propel the community and university dynamics towards better living conditions of the inhabitants, the participants of the workshops elaborated solutions to the social, environmental and economic problems raised. These solutions are formulated in the form of projects that can act as living laboratories in which researchers, local elected representatives, community organizations and other actors can interact and heal the ills of the Bambey commune of the UADB by reinforcing the dynamics of participatory governance, one of the prerequisites for implementing the SDGs in places like Senegal.